ANALYSIS OF TURNOVER INTENTION, WORK ENGAGEMENT, PERCEIVED ORGANISATIONAL SUPPORT AND HAPPINESS IN A PUBLIC SECTOR - Fritz Okta Nehemnya; Madju Yuni Ros Bangun (CV. Radja Publika, 2023)
The public sector in Indonesia is often regarded as a sector with stable employee turnover, possibly considered almost non-existent. However, the VUCA (volatile, uncertain, complex, and ambiguous) era has exerted pressure on employees within the Ministry of Finance (MoF) due to both global pressures (e.g., low economic growth) and domestic demands (e.g., high expectations for public services and societal way of life). The high job demands and societal pressures on employees at the MoF have created an exceedingly demanding work environment. Therefore, the research measures turnover intention (TI) which is found extremely high according to internal surveys (46%). This study explores the factors contributing to the high TI by predicting work engagement (WE), perceived organisational support (POS), and happiness as independent variables. Research data was collected through surveys (n=183) and analysed using Partial Least Squares, Structural Equation Modelling (PLS-SEM). The findings demonstrate the diverse impacts of WE (2.881>1.96 t-table; sig 0.004<0.10), POS (3.305>1.96 t-table; sig 0.001<0.10), and happiness (1.541<1.96 t-table; sig 0.123>0.10) to TI. Two hypotheses were supported, while one hypothesis was rejected, indicating the need for further research in the public sector environment.